Biomaterials for Tissue Engineering. - Razavi, Mehdi (Frontiers in Biomaterials., 2017)
This volume reviews the published knowledge about bioactive composites, protein scaffolds and hydrogels. Chapters also detail the production parameters and clarify the evaluation protocol for analysis or testing and scaffolding biomaterials. The volume concludes with a summary of applications of porous scaffold in medicine. Each chapter links basic scientific and engineering concepts to practical applications for the benefit of the reader. The text offers a wealth of information that will be of use to all students, bioengineers, materials scientists, chemists and clinicians concerned with the properties, performance, and use of tissue engineering scaffolds -- from research engineers faced with designing the biomaterials and techniques to physicians and surgeons charged with shepherding the use of the scaffolds into the applied clinical settings.